Indications and outcomes of abdominal surgery in patients with Crohn s Disease attending a tertiary hospital: a single centre study - Mabobo, Ndumbwe (Department of Medicine, 2024)
Background: Crohn's disease is a chronic inflammatory and heterogenous condion affecting predominantly the small bowel. Despite optimal medical therapy, it is associated with lifethreatening complications related to inflammation or fibro-stenotic disease that often require surgery. The aim of this study was to describe the characteristics of a cohort of patients with Crohn's disease requiring abdominal surgery. Methods: This was a retrospective study of adults attending at the colorectal unit of a teaching hospital. Relevant demographic and clinical data were collected from multiple sources from January 2010 to June 2020. Results: Sixty nine patients (4.6%) of the total cohort of IBD patients with Crohn's disease underwent abdominal surgery. The mean age at disease diagnosis was 27.9 ± 13.3 and mean age at time of surgery 43±13.2. Sixty-eight percent were females and 66% smokers. Thirty-three percent and 18.9% had fistulizing and stricturing disease respectively. Pre-operatively, 22% of patients were on steroids, 47% on azathioprine and 10% on biologics. The commonest indication for surgery was small bowel obstruction (37.6%), followed by fistulizing disease (18.8%). Sixty one percent of patients had one surgery, with a quarter needing more than two surgeries in the study period. Post-operative clinical recurrence occurred in 50%. Conclusions: Fifty two percent of patients had penetrating and/or stricturing disease necessitating surgery in a high proportion of patients. The commonest indication was small bowel obstruction. Post-operative recurrence was the commonest complication in half the patients. This data together speaks to the aggressive phenotype of CD in this cohort, and the important role that surgery still plays in the management of CD. A multi-disciplinary team is crucial in the management of these patients.